2013
DOI: 10.1589/jpts.25.1193
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation between Dynamic Balance Measures and Stance Sub-phase COP Displacement Time in Older Adults during Obstacle Crossing

Abstract: [Purpose] This study examined the relationship between the center of pressure (COP) displacement time during the stance subphases and dynamic balance ability when elderly cross obstacles 0, 10, and 40 cm in height. [Subjects] Fifteen older adults were enrolled in this study (≥65 years of age). [Methods] An F-Scan System was used to measure the COP displacement time when subjects crossed obstacles 0, 10, and 40 cm in height, and the Dynamic Gait Index, Berg Balance Scale, and Four Square Step Test were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 23 publications
(26 reference statements)
3
12
0
Order By: Relevance
“…That is, individuals with a lower BBS also had a lower DGI, indicating poorer overall mobility and balance control. This finding was in agreement with previous studies where positive correlations were reported between BBS and DGI in post-stroke individuals (e.g., Jonsdottir and Cattaneo, 2007; Nott et al, 2014), older adults (Park et al, 2013) and individuals with vestibular dysfunction (Whitney et al, 2003). Also, MoS (sum from both legs) and the range of H were positively correlated.…”
Section: Discussionsupporting
confidence: 93%
“…That is, individuals with a lower BBS also had a lower DGI, indicating poorer overall mobility and balance control. This finding was in agreement with previous studies where positive correlations were reported between BBS and DGI in post-stroke individuals (e.g., Jonsdottir and Cattaneo, 2007; Nott et al, 2014), older adults (Park et al, 2013) and individuals with vestibular dysfunction (Whitney et al, 2003). Also, MoS (sum from both legs) and the range of H were positively correlated.…”
Section: Discussionsupporting
confidence: 93%
“…However, it is not clear if this is actually 52 effective in terms of compensating for a decrease in stability or will 53 even further increase the risk of a fall. A conservative strategy 54 results in a slower walking speed when crossing an obstacle, which 55 in turn increases the time the centre of pressure (CoP) displaces 56 under the trailing foot (Park et al, 2013). Consequently, the dis-57 tance between CoP and centre of mass (CoM) at the instant of obstacle crossing is smaller resulting in decreased forward angular momentum.…”
mentioning
confidence: 99%
“…Our results demonstrate that independent of age, TT, S1, and S2 increased while crossing an obstacle. An explanation of these ndings consists of the fact that stepping over obstacles increases gait challenges at every age, even in the middle-age population [21,22]; however, this motor task is still more demanding for the elderly compared to young adults [23]. Previous studies reported that the elderly used a more conservative strategy for crossing obstacles relative to young adults, including a slower crossing speed and higher foot clearance while crossing over obstacles [24,25].…”
Section: Discussionmentioning
confidence: 99%